Cut Cortical Screw Purchase in Diaphyseal Bone: A Biomechanical Study - Wendling, Alexander; White, Joel; Cooper, Benjamin; Corrigan, Chad; Dart, Bradley (Kansas Journal of Medicine, 2022)
Introduction. During fracture osteosynthesis, traumatologists may remove screws which are too long, cut the excess length from the screw tip, and then reinsert the cut screw (CS) to minimize implant waste. The purpose of this study was to determine if this practice has an effect on screw purchase.Methods. Using an axial-torsion load device, we measured the maximal insertion torque (MIT) required to insert 3.5 mm stainless steel cortical screws into normal and osteoporotic bone models.  MIT was determined in three different test conditions: (1) long screw (LS) insertion; (2) LS insertion, removal, and insertion of a normal-length screw (NS); and (3) LS insertion, removal, cutting excess length from the screw tip, and reinserting the CS.Results. In the normal bone model, mean (± SD) MIT of LS insertion was 546 ± 6 N-cm compared to 496 ± 61 N-cm for NS reinsertion and 465 ± 69 N-cm for cut screw reinsertion.  In the osteoporotic bone model, MIT of LS insertion was 110 ± 11N-cm, whereas the values for NS and CS reinsertions were 98 ± 9 N-cm and 101 ± 12 N-cm, respectively.  There was no significant difference in MIT between CS and NS reinsertions in the osteoporotic bone analog.Conclusions. Cutting excess length from a 3.5 mm stainless steel cortical screw does not decrease its purchase regardless of bone density.  During osteosynthesis, orthopaedists may remove screws which are too long, cut the screw tip, and reinsert the shortened screw as a cost-saving measure without compromising fracture fixation.